Implementasi Sistem Aplikasi dan Metode Pembelajaran Paikem Gembrot Berjas (Berbasis Jaringan Sosial) - Rayung Wulan; Eddy Saputra; Nur Ali (Universitas Indraprasta PGRI Jakarta, 2017)
The process of learning in the educational unit organized an interactive, aspirational, fun, challenging, motivating the students to actively participate and provide enough space to for innovation, creativity, and independence according talents, interests, and physical development, as well as psychological protégé.